2018
DOI: 10.1371/journal.pone.0197097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of computer-assisted navigation versus conventional total knee arthroplasty on the levels of inflammation markers: A prospective study

Abstract: Total knee arthroplasty (TKA) is a well-established modality for the treatment of advanced knee osteoarthritis (OA). However, the detrimental effects of intramedullary reaming used in conventional TKA for distal femur cutting are of concern. Avoiding intramedullary reaming with the use of computer-assisted navigation TKA can not only provide superior prosthetic alignment, but also mitigate perioperative blood loss and the dissipation of marrow emboli. We quantified local and systemic concentrations of inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that this technique can disperse fat emboli, increasing the risk for venous thromboembolism as well. The use of navigation can reduce the invasiveness of the procedure by avoiding violation of the intramedullary canal, mitigating blood loss and dissipation of marrow emboli 29 . Furthermore, Kuo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that this technique can disperse fat emboli, increasing the risk for venous thromboembolism as well. The use of navigation can reduce the invasiveness of the procedure by avoiding violation of the intramedullary canal, mitigating blood loss and dissipation of marrow emboli 29 . Furthermore, Kuo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some studies have proposed that bleeding from trimmed cancellous bone of an uncovered resection surface [5,25,26] and a soft tissue surface [3] may be more significant sources of bleeding after TKA. It has also been suggested that intramedullary reaming and insertion of conventional instruments may inevitably lead to the destruction of endothelial cells, and dissipation of marrow emboli, which may subsequently induce a more inflammatory response and risk of embolismassociated morbidities such as acute cardiac disorders [7,27,28]. Accordingly, some inflammatory markers have been shown to be associated with functional recovery and morbidities following some major orthopedic surgeries [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that the higher the number of boluses of TXA, the lower the level of IL-6 and CRP. In CAS-TKA, Kuo et al [29] highlighted lower levels of systemic and local inflammatory markers than were observed in conventional TKA. According to the existing literature, inflammatory markers not only predict major complications, such as pneumonia, infection, or cardiovascular events, after orthopedic surgeries, but are also correlated with functional recovery after total joint arthroplasties [3032].…”
Section: Discussionmentioning
confidence: 99%